Modulating CoFeOX Nanosheets Towards Enhanced CO2 Photoreduction to Syngas: Effect of Calcination Temperature and Mixed‐Valence Multi‐Metals. Issue 72 (8th November 2022) - Pan, Bao; Zhou, Linxing; Qin, Jiani; Liao, Miao; Wang, Chuanyi
Abstract: CoFeOX nanosheets were synthesized by a facile coprecipitation and calcination method. The effect of calcination temperature on the crystal texture, morphology and surface areas of CoFeOX were fully explored. CoFeOX sample calcined at 600 °C (CoFeOX ‐600) showed superior catalytic performance for the reduction of CO2 under visible light. Compared with the pure Ru(bpy)3 2+ ‐sensitized CO2 reduction system, the CoFeOX ‐added system achieved 19‐fold enhancement of CO production (45.7 μmol/h). The mixed valence state and nanosheet‐like structure of CoFeOX cocatalyst support its ultra‐high charge transfer and abundant CO2 active adsorption sites exposure, which promote the separation of photogenerated charges, and thus improve the photocatalytic CO2 reduction activity. Carbon source of CO from CO2 was verified by 13 CO2 isotopic labelling experiment. Repeated activity experiments confirmed the good stability of CoFeOX in the CO2 photoreduction system. This work would provide prospective insights into developing novel cost‐effective, efficient, and durable non‐precious metal cocatalysts to improve the efficiency of photocatalytic reduction of CO2 . Abstract : The mixed valence state and nanosheet‐like structure of CoFeOX cocatalyst support its ultra‐high charge transfer, abundant CO2 active adsorption sites exposure, and thus outstanding photocatalytic CO2 reduction activity.